Evaluation of satisfaction and preference in patients with osteoporosis receiving Denosumab - Betül Sargın (National Scientific Medical Center, 2021)
Objective: Satisfaction and  preference  properties  differs  in  osteoporosis  treatment agents. In our study  we  aimed  to  evaluate  these  properties  in  patients  receiving  denosumab   treatment. Materials  and  Methods: Thirty female  patients who  had  denosumab  injections  were  included in our study. Demographic and general characteristics were recorded. General  patient  satisfaction, patient  satisfaction  of  the  drug  and  it's   effect  on   quality  of life was  evaluated on a Likert  scale. Patients'  preference  was  evaluated  with  asking  the   reasons  of  switches  to  denosumab. Results: The  mean  age  of  patients  was  59.30±12.86  years. Of   the  patients  30 (% 100.0) wanted to  continue  the  same therapy, 25 (%83.3) patients  stated  that  managing  this   treatment  is  extremely  easy. 25 (% 83.3) patients  stated  that  it  was  extremely  well-suited with  lifestyle.25 (% 83.3) patients  were  extremely  convenient  to take  medication.25 (%  83.3) patients have  extremely willed  to  continue  to  use  the  medication. Of  30 patients, 30(% 100) have been switched to denosumab due  to  physician  recommendation. Physician   recommended have been done to these patients due to ineffectivity of   previous  osteoporosis   treatments  or  due  to  side  effects  of   previous  osteoporosis  treatments. 22 (%73.33)  of   these patients have been  switched to denosumab due to ineffectivity of previous  osteoporosis treatments. About  8 (%26.66) patients have  been  switched  to denosumab due to side    effects  of  previous  osteoporosis treatments. Conclusion: Denosumab treatment in osteoporosis is a convenient and well-tolerated   therapeutic modality.